Association of maternal serum c-reactive protein with pre-eclampsia among patients attending in the outpatient department of a tertiary care hospital - Nesa, M. Karimatun; Daise, Tahmina Afreen; Ahmed, Naorin; Das, Kaberi; Haider, Chowdhury Afsana; Eva, Nusrat Jahan; Nahar, M. Irin; Khan, Farzana Farhin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia is a pregnancy-specific hypertensive disorder associated with systemic inflammation and endothelial dysfunction. C-reactive protein (CRP), an acute-phase reactant, is a potential biomarker for detecting and assessing preeclampsia severity. This study aimed to evaluate the association between maternal serum c-reactive protein (CRP) levels and preeclampsia. Methods: This case-control study was conducted in the department of obstetrics and gynecology, Institute of Child and Mother Health (ICMH), Dhaka, Bangladesh, from March 2023 to February 2024. This study included 70 pregnant women with a gestational age of 20-40 weeks. Among them, 35 women diagnosed with pre-eclampsia were assigned as cases, and 35 normotensive pregnant women were taken as controls. Results: Mean age and height were similar between groups, but preeclamptic women had significantly higher weight compared to controls (67.46±9.85 kg versus 57.26±9.27 kg; p=0.001). Elevated serum CRP levels were observed in 94.3% of preeclamptic patients, whereas all controls (100%) had normal CRP levels (p<0.001). The mean CRP was significantly higher in cases (25.37±14.70 mg/dl) than controls (4.22±0.92 mg/dl; p<0.001). A strong positive correlation was found between CRP and systolic blood pressure (r=0.822, p<0.001) and diastolic blood pressure (r=0.792, p<0.001). Conclusions: This study demonstrated a significant association between elevated maternal serum c-reactive protein (CRP) levels and preeclampsia, with a strong positive correlation to blood pressure. Elevated CRP may serve as a useful biomarker for early detection and monitoring of preeclampsia.